Improving food safety in the informal sector: Nine years later - Grace, Delia; Dipeolu, M.; Alonso, Silvia (Informa UK Limited, 2019)
Introduction: Foodborne disease is a major public health problem in poor countries, but we lack effective, sustainable and scalable approaches that work in the traditional, informal markets where most fresh, risky food is sold. A promising intervention is working with informal sector vendors to provide: a) training and technologies; b) an enabling environment; c) motivation for behaviour change. Materials and methods: We present a long-term follow-up of pilot project in one of the largest abattoirs and meat markets in Nigeria. An evaluation shortly after implementation found the intervention was acceptable, cost-effective and resulted in safer meat. The follow-up nine years later using mixed methods: qualitative surveys and microbiological tests. Results and Discussion: The policy environment had become disabling, partly as a result of authorities attempts to move butchers to a modern, hygienic but more distant abattoir. This was resisted by the butchers. Authorities revoked the license for Bodija market and stopped providing services. Matters escalated and forceful attempts to remove butchers resulted in deaths followed by riots. Meat safety deteriorated. Conclusion: The case study shows the importance of an enabling environment and need for stakeholder collaboration in attempting to improve food safety in the traditional sector.